2022
DOI: 10.3389/fimmu.2022.994823
|View full text |Cite
|
Sign up to set email alerts
|

Basophils activation of patients with chronic spontaneous urticaria in response to C5a despite failure to respond to IgE-mediated stimuli

Abstract: Urticaria is characterized by the occurrence of wheals and flares in response to vasoactive mediators, such as histamine. Various studies have suggested the involvement of basophils in the pathogenesis of chronic spontaneous urticaria (CSU). However, histamine release from peripheral basophils in response to stimuli acting on the high affinity IgE receptor (FcϵRI) is impaired in many patients with CSU (non/low responders). We previously demonstrated that tissue factor (TF)s expressed on vascular endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Basophils of CSU patients exhibited significantly higher amounts of CD63, than those of healthy controls. CD203c expression however was unchanged (88). In contrast, another study revealed no difference of activation marker levels in CSU patients in comparison with healthy subjects.…”
Section: Chronic Spontaneous Urticariamentioning
confidence: 84%
See 1 more Smart Citation
“…Basophils of CSU patients exhibited significantly higher amounts of CD63, than those of healthy controls. CD203c expression however was unchanged (88). In contrast, another study revealed no difference of activation marker levels in CSU patients in comparison with healthy subjects.…”
Section: Chronic Spontaneous Urticariamentioning
confidence: 84%
“…In contrast, another study revealed no difference of activation marker levels in CSU patients in comparison with healthy subjects. However, histamine release was reported to be higher in patients with CSU than in controls ( 89 ). In CSU patients in remission, basophils were more activated, as determined through the presence of CD63 and CD203c, than in healthy control ( 90 ).…”
Section: Chronic Spontaneous Urticariamentioning
confidence: 99%
“…Several basophil characteristics and their behavior in CSU patients are summarized in Table 1 . In a group of patients, the concentration of histamine in the plasma of patients with CSU was significantly higher than that of healthy controls ( Table 1 ) [ 31 ]. Moreover, spontaneous histamine release from basophils without stimulation in patients with CSU was increased, compared to that in healthy donors ( Table 1 ) [ 31 , 32 ].…”
Section: Basophil-related Molecules In Plasma and On Cell Surface Of ...mentioning
confidence: 99%
“…In a group of patients, the concentration of histamine in the plasma of patients with CSU was significantly higher than that of healthy controls ( Table 1 ) [ 31 ]. Moreover, spontaneous histamine release from basophils without stimulation in patients with CSU was increased, compared to that in healthy donors ( Table 1 ) [ 31 , 32 ]. Nevertheless, the degree of spontaneous release of histamine was not correlated with total amount of histamine in the whole blood of patients with CSU [ 31 ], suggesting that the percent release of histamine from individual basophils of patients with CSU is higher than that of healthy control.…”
Section: Basophil-related Molecules In Plasma and On Cell Surface Of ...mentioning
confidence: 99%
See 1 more Smart Citation